Bentuk Dan Strategi Perupaan Mural Di Ruang Publik - Syamsiar, Syamsiar (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2009)
Mural now familiar to resi-dents of the city, almost in every street corners is murals with a wide range of visualization. The road users would not want to accept the existence of these murals. Two adjacent cultural city as a focus of research has a picture of the existence of the creation of the mural as follows: 1) The form and content according to envi-ronmental conditions, 2) Mural in form and content does not comply with the environmental conditions. 3) murals that have no clear goal and collided with the graffiti. The strategy needs to be done in the creation of murals, for suitable for public spaces are: 1) Workers mural art or artists should have experience in work-ing on the mural, 2) the idea or content of the mural should be considered in depth and tho-rough, to be more appropriate and beneficial to the wider community, 3) Visually (shape or form) should contain murals created aesthetic value as the comparison between the images with road users can be seen clearly. 4) Good collaboration with municipalities, and relevant par-ties would further support the implementation process of mural making 5) With the holding of the race course will also affect the variation of the mural that was created, because each group or individual has a different cha-racter-creation different, 6) Age mural tends to be short compared with other conventional works, because it works more on outdoor murals, so the weather was affecting the continuance. 7) In the mural creation strategies, will vary with the creation of conventional painting, because the mural visualization tend to occupy a vast space and some-times high, so that the necessary technical perspective and a more powerful distortion.Â Keywords: Mural, teknique and public art